Análisis de guion y personajes de los programas de televisión producidos por wwe: raw y smackdown, para conocer su fórmula de éxito. Periodo de investigación: junio - julio de 2020 - Medina Lanchi, Darwin Stalin (2021)
The present research work was carried out in order to analyze and know the formula for success that the RAW AND SMACKDOWN programs of the WWE franchise have, taking into account that among the main elements for the programs to be popular are mainly the production models, based on the scripts and characters that act in the presentations. It is known that there are many programs that have failed in the attempt, but the WWE has been maintained throughout years and generations, providing entertainment to families locally and internationally, but it is known that beyond its popularity, one of the main elements to give a plot and entertain people is based on the scripts that are executed. After having carefully observed all its programming during the period of June - July 2020, the scripts, characters and their dramatic action were analyzed. The justifications were made in all its aspects, and the bibliographic review with topics that served as support to develop the present analysis was confirmed, The scientific method was used in order to obtain a wide knowledge of the subject to be treated, The research is of a exploratory, knowing that through this method the analysis of a little studied and at the same time novel topic was carried out, taking into account that a broad analysis of the object to be studied was required, in order to carry out a more complete investigation. Its approach is qualitative, since the technique of observation sheets was applied, which served to collect enough information from WWE programs, analyzing each program and event of both RAW and SMACKDOWN during the June-July period of 2020, in order to know the formula for success that they have had and continue to have today. The execution of all this investigative work was supported by a schedule of activities and material, intellectual and economic resources that made the successful completion of this investigation possible.